The relationship between self-control and tax aversiveness and students' academic procrastination - Indra Saputra; Firman Firman; Dea Aulia (Global Econedu, 2026)
Academic procrastination is a common phenomenon that negatively impacts student achievement. This study aims to examine the relationship between self-control and task aversiveness on students' academic procrastination. The study was conducted using a quantitative correlational approach on 285 students of SMA Negeri 8 Padang City who were selected using proportional stratified random sampling. Data were collected using a questionnaire and analyzed through simple linear regression. The results showed that self-control had a significant negative relationship with academic procrastination, while task aversiveness had a significant positive relationship with academic procrastination. These findings confirm that low self-control and high perceptions of task uninterestingness contribute to increased procrastination. The practical implications of these results can be the basis for developing guidance and counseling services to improve self-control and reduce task aversiveness.